Uji Efek Antipiretik dan Antiinflamasi Ekstrak Etanol Buah Pare (Momordica charantia L.) terhadap Mencit Jantan - Parawansah Parawansah; Wahyuni Wahyuni; Zakiyatul Mahmudah (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2016)
This research was carried out to determine the content of secondary metabolites contained in the ethanol extract of bitter melon (Momordica charantia L.) and antipyretic and antiinflammatory effects on mice. Bitter melon extract obtained by maceration method using ethanol 96%. Bitter melo ethanol extract was made in three variations of dose 50 mg / KgBW, 150 mg / KgBW, and 250 mg / KgBW. The content of secondary metabolites determined phytochemical Skrining by TLC (thin layer chromatography) with specific reagent. Antipyretic effect performed by vaccine DPT (Diphtheria Pertussis Tetanus) as inducers of fever and Parasetamol 500 mg as a positive control and antiinflammatory effect using the method of edema artificial on the soles of the mice foot with carrageenan 2% as an aphrodisiac edema and Diclofenac Sodium 50 mg as a positive control. Subjects used is a white male mice were given intraperitoneally (i.p). Analysis of the data using ANOVA statistical analysis and continued with LSD Post Hoc test. Phytochemical screening results showed that ethanol extract of bitter melon contains alkaloids, tannins, flavonoids, saponins, and triterpenoids. The results indicated that ethanol extract of bitter melon at dose of 150 mg/KgBW has antipyretic effect with total temperature decrease 1,1oC and anti-inflammatory effects with the largest of inflammation inhibition percent by 68.57%. One way ANOVA analysis signify a probability value (p) < 0.05 with 95 % of confidence level that indicate a significant influence of ethanol extract of bitter melon to its antipyretic and antiinflammatory effects on male mice.Keywords : Antipyretic, Anti-inflammatory, Momordica charantia, Bitter melon